Flavitrack analysis of the structure and function of West Nile non-structural proteins. (11th March 2010) - Danecek, Petr; Schein, Catherine H.
The Flavitrack database groups Flaviviruses (FV), evolutionarily related organisms with high subtype variability, according to their phenotypes. Here, PCPMer tools were used to calculate consensus sequences based on conservation of Physicochemical Properties (PCP) for 919 sequences of NS2a, a non-structural protein involved in preventing host interferon response to infection. Conserved PCP-motifs were detected, primarily in the N-terminal half of NS2a. One model structure, based on a nuclear receptor, groups residues essential for West Nile (WN) infectivity (I59, V61, and M103) in a pocket on the protein surface. These methods will aid in the design of vaccines and specific therapies against FV.